Comparing of thermal and cold plasma non-thermal pasteurization on bioactive compounds and microbial load of red orange juice (Sanguinello L.) - A. Olyaee; Sh. Berenjy; L. Nateghi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2022)
Non-thermal methods are introduced to lessen the color degradation and loss of nutritional compounds in fruit juices caused by conventional thermal pasteurization. This research aimed to investigate the effect of cold atmospheric gas phase plasma on physicochemical properties, bioactive compounds, and microbial load of red orange juice. The results show a significant difference (p≤ 0.05) between the samples treated with cold plasma and thermally pasteurized ones, in terms of physicochemical characteristics (acidity, pH, Brix, and color), bioactive compounds (anthocyanin, total phenol, and vitamin C) and microbial load (yeast/mold population and aerobic bacteria). The microbial load in the samples treated with cold plasma was within the acceptable range approved by the Iranian National Standard. The highest values of bioactive compounds (anthocyanin 51.248 mg/l, total phenol 1988.2 mg/l, and vitamin C 398 mg/l) were observed in the cold plasma pasteurized sample (at 20 kV, for 10 min and atmospheric gas). These values were significantly (p≤ 0.05) higher than those of thermally-pasteurized samples. The results showed that by applying the cold plasma process for the pasteurization of red orange juice, along with obtaining a healthier product, more bioactive compounds are preserved.